ANALISIS PROFIL KONSUMEN PADA USAHA FERRY CATERING DI MASA PANDEMI - Shania Artamevia; Nadya Novandriani Karina Moeliono (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2022)
The economic impact of the Covid-19 pandemic has been felt globally by various businesses, one of which is the Ferry Catering culinary business, which caters for big events. Turnover has dropped dramatically where the biggest contribution to Ferry Catering was wedding catering which is not running smoothly as it used to be due to the pandemic. Thus, Ferry Catering plans to focus on daily catering. The purpose of this research is to find out whether customers in the daily segment exist and can be used as one of the segments that can be served by Ferry Catering during this pandemic period to replace the previous lost revenue by formulating customer jobs, pains, and gains through the Value Proposition Design approach by Alexander Osterwalder. Used a descriptive qualitative method that conducts interviews, non-participant observation, and documentation. The final result of this research is what consumers do, namely buying food out, seeking information through friends' recommendations. Things that disturb consumers, namely worrying about the protocol that the catering services do, the menu does not vary. Then for things that customers want are the catering price according to quality, strong packaging so that it is not easily contaminated with viruses